Cryptogenic organized pneumonia in the immediate puerperium. Retrospective analysis of a clinical case (La U Investiga, 2023)
Cryptogenic organized pneumonia is a type of organized pneumonia of unknown cause. Its diagnosis is by exclusion and should be made based on clinical suspicion, axial tomography findings and response to treatment, mainly with corticosteroids. A clinical case of a 40-year-old female patient is described who, during the immediate puerperium and after an iterated cesarean section, developed an event of severe dyspnea, accompanied by low oxygen saturation. A computerized axial tomography was performed, showing an interstitial lung pattern compatible with organized pneumonia. By ruling out other probable etiologies, it was decided to start treatment based on corticosteroids, with which a favorable response was quickly obtained, thus confirming the diagnosis of cryptogenic organized pneumonia in the immediate puerperium. Therefore, it is considered that the entity that is the object of our discussion can present in unusual contexts such as pregnancy or the puerperium and adequate treatment with corticosteroids will avoid complications and recurrences.
Keywords: Corticosteroids, dyspnea, cryptogenic organized pneumonia, puerperium.